Sickness of neonates of recently delivered women and their referral in Uttar Pradesh, India - Tripathy, Tridibesh; Das, Shankar (International Journal Of Community Medicine And Public Health, 2020)
Background: The current study done in 2017 explores some of the crucial variables of the type of problems of the newborns as reported by their mothers. The mothers also responded about the type of personnel who referred their newborns. The responses of these mothers or recently delivered women (RDW) (as named for the current study) had a 3 to 6 months old child during the time of survey. They were selected as respondents as they were in a position to recollect the events of their children during their newborn period. Methods: A total of four districts of Uttar Pradesh were selected purposively for the study and the data collection was conducted among the RDWs in the villages of the respective districts with the help of a pre-tested structured interview schedule with both close-ended and open-ended questions. These in-depth interviews were conducted amongst the RDWs and a total 500 respondents participated in the study. Results: The results reflected that more than 97% RDWs reported fever as the problem of their newborn in Banda, Gonda and Barabanki districts except Saharanpur where 82% RDWs reported fever in their newborns. Another major problem of newborn across the 4 districts was ‘unable to take feeds. The results as per the response of the RDWs in all the four districts demonstrated that ASHA was the personnel who referred the maximum number of their newborns. Conclusions: To conclude, fever was the leading cause of health problem as identified by the RDWs and mostly ASHAs referred the majority of the newborns.